Pengembangan Media Website Guru Bahasa Arab dalam Proses Belajar Mengajar Materi Qiraah - Moh Firdaus; N. Hula, Ibnu Rawandhy; Bt. H. Bahri, Ratni (ELOQUENCE : Journal of Foreign Language, 2023)
Background: The rapid development of technology today requires teachers to keep up with the flow of information including the development of learning media. Purpose: This study was conducted to determine the development and quality of the teacher's website media in the Arabic language teaching and learning process and to determine the effectiveness of the use of Arabic language teacher website media in the teaching and learning process at MTs N 1 Gorontalo Regency. Method: This research uses the ADDIE development model, which stands for Analysis-Design-Development-Implementation-Evaluation. This model was developed by Dick and Carry which is arranged programmatically with a regular sequence of activities in an effort to solve learning problems related to website media tailored to the needs of teachers and the characteristics of students. Results: The product developed is the Arabic language teacher's website media in the Arabic language teaching and learning process at MTs N 1 Gorontalo Regency. the determination of sampling and samples was taken from class VII.5 totaling 25 students and one Arabic language teacher. Conclusion and Implications: This study showed that the Arabic language teacher's website at MTs N 1 Gorontalo Regency effectively enhanced teaching. With strong student (88.9%) and teacher (85%) responses, it could serve as a model for developing tech-based learning media in other subjects and support integrating technology into the curriculum to boost student engagement and learning outcomes.